Green Human Resource Management Research Landscape: Trends, Gaps, and Future Directions from a Systematic Literature Review - Priskilla E.E. Napitupulu; Yanuar Dananjaya; Hananiel M Gunawan (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
Green Human Resource Management (GHRM) has emerged as a vital organizational approach that aligns human capital practices with environmental sustainability. This study investigates publication trends, thematic orientations, and methodological patterns within GHRM research while identifying key theoretical and practical gaps. Using bibliometric evidence from Scopus between 2013–2025, the analysis highlights a sharp increase in scholarly attention after 2018, dominated by studies in Asia, particularly China, India, and Malaysia. The findings suggest that most works adopt the Ability–Motivation–Opportunity (AMO) and Social Exchange Theory as dominant frameworks, with limited exploration of broader institutional or stakeholder-based approaches. In addition, research gaps remain concerning cross-cultural validation, longitudinal analysis, and practical implementation challenges in organizations. The study contributes by proposing future research directions that connect GHRM to sustainable organizational performance, innovation, and resilience. Ultimately, this research underscores the significance of integrating environmental and human resource strategies to achieve long-term sustainability.